Compact Eyeshadow Preparations from Chiken Egg Shell and Rosella Flower Petals Extract (Hibiscus Sabdariffa L) as Natural Colorants and Preservatieves - Agustin, Eny Widhia; Wara Dyah Pita Rengga (Rekayasa, 2022)
Eyeshadow is used to give the eye dimension to look attractive, so the selection of eyeshadow materials needs to be considered to avoid side effects that can occur on the surface of the eyelids. Eyeshadow can be made from natural ingredients. One of the natural ingredients that can replace talcum chemicals is chicken eggshell powder because chicken eggshell powder contains a source of calcium that can nourish the skin. Rosella flower petal powder extract is also added as a natural colourant for manufacturing this compact eyeshadow powder. In addition to functioning as a colourant, Rosella flower petals contain anthocyanins and flavonoids, which have antioxidant and antibacterial properties. This study aims to determine the innovation process of chicken eggshell waste into Compact Powder Eyeshadow as decorative cosmetics by analyzing the feasibility of eyeshadow through organoleptic tests, pH tests, particle uniformity tests, specific gravity tests, and water content tests. This study's results show that formula III's physical quality with an extract concentration of 50% has good physical quality compared to other concentrations because the resulting colour is light. However, the colour resistance produced is the same as other formulas and does not last long.